Christmas with Morris and Boris - Wiseman, Bernard (Boston : Little, Brown, 1983)
Boris tries to explain Christmas to Morris but has little success until Billy and Laura invite them to spend Christmas Eve at their house.
Keywords: Christmas -- Fiction; Moose -- Fiction; Bears -- Fiction